Hubungan Self-efficacy Akademik dan Motivasi Berprestasi Terhadap Hasil Belajar di SMA Budi Murni 1 Medan - Cindy Meiliana Putri Sibarani; Togi Fitri A. Ambarita (Visi Sosial Humaniora, 2022)
The final score of learning process at school influenced by internal factors within students, include academic self-efficacy and need of achievement. Academic self-efficacy is individual belief in their ability to carry out their duties; while the achievement motivation possessed students to obtain success in school. Students with good academic self-efficacy and strong achievement motivation within themselves tend to be successful in achieving satisfactory learning results. This study aims to determine the relationship between both academic self-efficacy and achievement motivation toward the final score of learning process in school. This research uses quantitative methods. This research was conducted at SMA Budi Murni-1 Medan with students in class X I and X I I I, P A and I P S. The total population was 512 people, of which 200 people were used as sample by uses Gpower application. The data collection tool used the academic self-efficacy scale and the achievement motivation scale. Student’s final score are obtained from report cards. Data analysis using multiple correlation test by SPSS. The results of data analysis find score r = 0.21; with a significance level of 0.012. The significance or p obtained was 0.012 or p <0.05; then the hypothesis in this study is declared accepted, meaning that there is a significant correlation between academic self-efficacy and achievement motivation toward academic achievement at SMA Budi Murni -1 Medan. The relationship or correlation of achievement motivation and self-efficacy (simultaneous) toward final score is 0.21.